COMMUNITY INFORMATION CENTRE: PUBLIC LIBRARY BIHAR - Shweta Kumari (International Journal of Multidisciplinary Research and Studies, 2021)
The level of education that a country gives its residents is the single most important factor in determining the overall quality of its population. Education is one of the most important factors in the development of a society. It is the process by which humankind is working out into friction of its own inner nature. It is the way by which a man may realise his destination of accomplishing his aim of greatest strength, greatest joy, and greatest service, so enabling him to develop into the maximum potential of his stature. As a member of the general populace of the area, one may have possessed. Learning for a lifetime, making autonomous decisions, and the growth of cultural traditions are all fundamentally facilitated by the community's presence in public libraries, which serve as "gateways to knowledge" in their respective communities. This Manifesto affirms UNESCO's confidence in the public library as an active force for the promotion of education, culture, and information, as well as a vital agent for the development of peace and spiritual well-being. via the thoughts of both males and females. Therefore, UNESCO encourages national and local governments to support the growth of public libraries and actively engage in this process.